The Impact of Work-Life Balance and Job Stress on Turnover Intention with Job Satisfaction as a Mediator at Regional Publuc Company Berintan Market Cirebon City” - An Nasya, Al Auliya; Tholkha, Muhammad Syarifath; Novandi, Devin Try; Hardjowikarto, Dharliana Ayu; Wibowo, Sandi Nasrudin (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
In an increasingly competitive job market, understanding the factors that influence employee retention is vital for organizations aiming to maintain stability and performance. The Regional Public Company Berintan Market in Cirebon City faces challenges related to employee turnover, which can disrupt operations and impact service quality. This study investigates the relationship between job satisfaction, work-life balance, workplace stress, and intentions to quit among its employees. Researchers used descriptive statistics and smart PLS version 4.1.0.1 to examine survey results from 71 employees. The study’s author concluded that elements like job happiness, work-life balance, stress at work, and the desire to leave everything go hand in hand. We discovered that work-life balance and workplace stress significantly affected the urge to quit one’s present job after we looked at the direct effects. Studies on mediation have shown that job satisfaction moderates the connection between workplace stress, work-life balance, and desire to leave. Helping workers companies may reduce employees’ intentions to quit their employment.